Candide, or, Optimism - Voltaire, 1694-1778 (Yale University Press, 2005)
"In this new translation of Voltaire's Candide, distinguished translator Burton Raffel captures the French novel's irreverent spirit and offers a vivid, contemporary version of the 250-year-old text. Raffel casts the novel in an English idiom that - had Voltaire been a twenty-first-century American - he might himself have employed. The translation is immediate and unencumbered, and for the first time makes Voltaire the satirist a wicked pleasure for English-speaking readers."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved